Thermodynamic modelling of Ti-Zr-N system. (March 2017) - Sridar, Soumya; Kumar, Ravi; Hari Kumar, K.C.
Abstract: Thermodynamic modelling of Ti-Zr-N system is performed using Calphad method coupled with ab initio calculations. The energies of formation of stable and metastable end-members of sublattice formulations of solid phases in Zr-N system and enthalpy of mixing of the mixed nitride (Ti, Zr)N ( δ ) are calculated using ab initio method. Phonon calculations are used to compute the Gibbs energies of stoichiometric ZrN and the mixed nitride δ . With the aid of experimental thermochemical and constitutional data from the literature along with the results of ab initio calculations, thermodynamic optimization is carried out to obtain the Gibbs energy model parameters. Abstract : Highlights: Experimental data and ab initio predictions used for modelling Zr-N system. Ti-Zr system re-optimized with recent experimental data. Ti-Zr-N system is modelled using ab initio generated thermochemical data. Critical point of miscibility gap matches with results from ab initio calculations.